Industrial Value Addition, Credit Growth and Economic Growth in Botswana - Jeke, Leward; Abel, Sanderson (International Journal of Economics and Financial Issues, 2025)
The sluggish economic growth trajectory in Botswana, characterized by subdued expansion in real GDP per capita, precipitates concerns regarding the efficacy of extant macroeconomic policies. Confronted with an imperative to diversify its economy and mitigate sectoral vulnerabilities, Botswana’s growth dynamics warrant scrutiny. This study endeavors to elucidate the determinants of economic growth in Botswana, identifying trade openness, savings rates, domestic credit to the private sector, and industrial value-added as pivotal factors exerting a positive influence on growth dynamics. The findings suggest that augmenting these variables can stimulate economic expansion, thereby underscoring the imperative for policymakers to craft targeted fiscal and monetary policies that foster a conducive business environment, optimize resource allocation, and catalyze sustainable economic development. By leveraging these insights, policymakers can devise evidence-based strategies to bolster Botswana’s economic resilience and enhance its growth prospects.